Accounting policy in Latvia – existing main rules and current trends - Bumane, Inga (Buhalterinės apskaitos teorija ir praktika, 2014)
The article reflects the study on the main aspects of the Directive of the European Parliament and of the Council 2013/34 / EU “On annual financial reports, consolidated financial reports and related reports of enterprises of certain types” (hereinafter referred to as the new directive), paying particular attention to the requirements put forward to micro enterprises . A comparative analysis of the requirements of the new EU directive and the existing main accounting rules in Latvia was also carried out. As a result of the study, recommendations were developed on problematic aspects that relate to accounting in Latvia due to the need to introduce the requirements of the new directive into national legislation.